Study of the perception of external auditors on the disclosure of ISR (Islamic Social Responsibility) in Islamic banking in Indonesia - Kadariah , Siti; Agus, Agus; Sugianto, Sugianto; Muda, Iskandar; Purnama Sari, Eka (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
This study aims to determine how the perception of external auditors in disclosing ISR (Islamic Social Responsibility) in Islamic banking in Indonesia. Islamic Social Reporting (ISR) from 2013-2016 was 87.50% which revealed 42 of the 48 ISR index items by Bank Muamalat Indonesia in 2013, 2014 and 2016 and Bank Syariah Mandiri in 2013 and 2016. Meanwhile, the value of minimum ISR disclosure of 52.10% which revealed 25 of the 48 ISR index items by BCA Syariah in 2013 and 2014).